Conifers depend on established roots during drought: results from a coupled model of carbon allocation and hydraulics. Issue 2 (5th August 2019) - Mackay, D. Scott; Savoy, Philip R.; Grossiord, Charlotte; Tai, Xiaonan; Pleban, Jonathan R.; Wang, Diane R.; McDowell, Nathan G.; Adams, Henry D.; Sperry, John S.
Summary: Trees may survive prolonged droughts by shifting water uptake to reliable water sources, but it is unknown if the dominant mechanism involves activating existing roots or growing new roots during drought, or some combination of the two. To gain mechanistic insights on this unknown, a dynamic root‐hydraulic modeling framework was developed that set up a feedback between hydraulic controls over carbon allocation and the role of root growth on soil–plant hydraulics. The new model was tested using a 5 yr drought/heat field experiment on an established piñon‐juniper stand with root access to bedrock groundwater. Owing to the high carbon cost per unit root area, modeled trees initialized without adequate bedrock groundwater access experienced potentially lethal declines in water potential, while all of the experimental trees maintained nonlethal water potentials. Simulated trees were unable to grow roots rapidly enough to mediate the hydraulic stress, particularly during warm droughts. Alternatively, modeled trees initiated with root access to bedrock groundwater matched the hydraulics of the experimental trees by increasing their water uptake from bedrock groundwater when soil layers dried out. Therefore, the modeling framework identified a critical mechanism for drought response that required trees to shift water uptake among existing roots rather than growing new roots. Abstract : See also the Commentary on this article by Santiago, 225: 599–600 .